A case report of unsuccessful VBAC in primary care: highlighting the lesson learned - Ummah, Nafi'atul; Agusfar, Achmad Zani; Musrifah, Siti (BKM Public Health and Community Medicine, 2024)
Purpose: To delve into the patient’s attempt at vaginal birth after cesarean section (VBAC) in the primary care center and to highlight the importance of the primary care center for women opting for VBAC. Methods: This case report describes a woman with unsuccessful VBAC in primary care. Informed consent was obtained before the study. Results: A woman in her mid-thirties with a history of a prior cesarean section and a failed trial of labor was referred to the hospital at 40 weeks gestational age due to prolonged labor. The patient was referred to the hospital after 14.5 hours of trial labor in primary care. After delivery, the patient had urinary retention caused by pelvic nerve injury. The newborn baby had an APGAR Score of 3/5 and was treated in the Neonatal Intensive Care Unit (NICU) with respiratory distress syndrome and meconium aspiration syndrome. Conclusion: Vaginal birth after cesarean can be done by considering its indications and contraindications. However, it is recommended to perform VBAC in hospitals equipped with emergency cesarean facilities, in which the cesarean section can be done within 30 minutes after the decision has been made. Primary care centers have a role in educating patients, providing guidance, and selecting patients for referral. This case also highlights the importance of a holistic approach to social obstetrics, addressing medical, social, economic, and systemic factors. By doing so, healthcare systems can ensure equitable access to timely and appropriate care, ultimately enhancing the well-being of pregnant women and improving VBAC success rates.